RIBOSOMAL IMMUNOCORRECTION EFFICACY ASSESSMENT - O.V. Iozefovich; Т.V. Chernyaeva; I.V. Fridman ("Paediatrician" Publishers LLC, 2011)
Respiratory pathology and acute respiratory infections make the major part of all pediatric diseases. This pathology is a matter of special importance especially in the group of frequently-sick children. This article contains information upon functional peculiarities of immune system, necessity of effective preventive measures development, or if protracted clinical course and treatment occur, recurrent respiratory diseases, as well as immunization of such children against the background of immunocorrection with ribosomal vaccine. Key words: acute respiratory infections, immunocorrection, ribosomal vaccine. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 107-110.)